Preparation method of modified graphene reinforced high-entropy alloy layered composite coating

Through the preparation method of layered composite plating of modified graphene enhanced high-entropy alloys, combined with chemical modification and electrodeposition technology, the problem of surface wear of key components in complex environments is solved, and the coating performance of high strength and high wear resistance is achieved, supporting online repair needs.

CN119776924APending Publication Date: 2025-04-08安徽恒利增材制造科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411814438.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When the existing technology solves the problem of surface wear of key components such as armored vehicle transmission systems, aircraft landing gear support shafts, and ship transmission systems in complex environments, the equipment covers a large area and is limited online repair, and the coating performance is difficult to meet the needs of high strength and high wear resistance.

Method used

The preparation method of layered composite plating with modified graphene enhanced high-entropy alloy is adopted. Through chemical modification technology and electrodeposition technology, combined with external field assisted technology, a high-strength, high-wear-resistant composite plating with a layered structure of shell pearls is prepared.

Benefits of technology

A high-strength, high-wear-resistant nanocomposite coating is achieved, which significantly improves the surface wear resistance of key components, reduces costs, and supports online repair needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776924A_ABST
    Figure CN119776924A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface coatings, in particular to a preparation method of a modified graphene reinforced high-entropy alloy layered composite coating, which comprises the following steps: step 1, graphene surface functionalization design and a directional regulation and control mechanism thereof; 2, a CoCrFeNi-M series high-entropy alloy coating is designed, and an electro-deposition mechanism is adopted; and 3, structural design and tribological behaviors of the modified graphene reinforced high-entropy alloy composite plating layer. The method has the following beneficial effects that the shell nacre body surface structure is simulated according to the wear-resistant protection performance requirements of key components such as an aircraft landing gear supporting shaft and a crankshaft, and the wear-resistant protection performance requirements of the key components such as the shell nacre supporting shaft and the crankshaft are met; through graphene surface functionalization design and external field auxiliary electro-deposition process innovation, the layered composite coating integrating high toughness and high wear resistance is designed and controllably constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing a modified graphene-enhanced high-entropy alloy layered composite coating, and belongs to the technical field of surface coatings. Background Art

[0002] Key components such as deformable thin-walled parts in armored vehicle transmission systems, aircraft landing gear support shafts, and crankshafts in ship transmission systems are subjected to complex environments such as mud, steam, and salt spray for a long time during service, which causes the surface wear of components to be particularly severe, seriously affecting the reliability and service life of service equipment, and thus causing huge economic losses. Therefore, it is extremely important to carry out surface wear protection work for these key components that are prone to failure. Surface coating technology is the most direct and effective way to solve the wear problem. At present, the most commonly used surface protection technologies for metal parts are chemical plating, electrodeposition (including brush plating), spraying, plasma cladding, and laser cladding. Among them, the equipment for spraying and cladding occupies a large area. Affected by the spatial characteristics of components and the requirements for in-situ repair, these two methods are restricted in terms of online maintenance of components. The brush plating technology developed based on the principle of electrochemistry has the characteristics of simple equipment, portability, fast deposition speed, multiple types of coatings, and low energy consumption. It shows unmatched advantages over other surface engineering technologies in the field of surface protection of service equipment, especially in the field of online repair. Therefore, considering the complex shapes and rapid repair characteristics of service equipment parts, brush plating technology has become the only choice for online repair of key parts of service equipment. In the electrodeposition process, the choice of coating system is the key to determining the performance of the coating. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a modified graphene enhanced high entropy alloy layered composite coating to solve the problems raised in the above background technology.

[0004] In order to achieve the above object, the present invention is implemented by the following technical scheme: a method for preparing a modified graphene enhanced high entropy alloy layered composite coating, comprising the following steps:

[0005] Step 1: Graphene surface functionalization design and its directional regulation mechanism;

[0006] Using chemical modification technology, systematically study the influence of multi-element and multi-scale metal particle loading on the physical properties (dispersion, magnetic properties) of graphene material composite powders;

[0007] Screen and prepare modified graphene composite powders that can be controlled by external field, and reveal the distribution characteristics of composite powders during external field-assisted electrodeposition;

[0008] Step 2: Design of CoCrFeNi-M high entropy alloy coating and its electrodeposition mechanism;

[0009] Based on the first principles, the crystallographic parameters, thermodynamic properties and physical properties of CoCrFeNi-M (M=Al, Cu, Mn) high entropy alloys are simulated and predicted, and the types of M principal elements in the CoCrFeNi-M system are optimized to provide theoretical guidance for the principal element design of electrodeposited CoCrFeNi-M high entropy alloy coatings.

[0010] The influence of solution parameters and electrodeposition process parameters on the microstructure and properties of high entropy alloy coatings was systematically investigated. Combined with thermodynamic calculations, the deposition mechanism of the solid solution phase in high entropy alloy coatings was clarified, and the corresponding relationship between the main element type / element content, process parameters and coating microstructure and properties was established to screen out high entropy alloy coating systems with good forming quality.

[0011] Step 3: Structural design and tribological behavior of modified graphene-enhanced high-entropy alloy composite coating;

[0012] Optimize the external field assisted electrodeposition process parameters, realize the controllable regulation of the distribution state of functionalized graphene composite powder in high entropy alloy coating, construct gradient layered composite coating, and explore the organizational structure evolution law and regulation mechanism of composite coating under the action of electric field and external field;

[0013] The influence of different tribological test conditions on the tribological properties of composite coatings is studied, and the surface wear state, defect form and changing characteristics of graphene structure of the composite coating after the friction test are examined. The mapping relationship between process parameters, coating structure and tribological properties is clarified, and the structural design and controllable construction process of the composite coating are optimized through feedback.

[0014] Specifically, chemical modification technology is combined with electrodeposition technology. Chemical modification technology is used to evenly load nano-metal particles on the surface of graphene. This is used as a precursor, and functionalized graphene-reinforced high-entropy alloy composite coatings are prepared by optimizing the electrodeposition process parameters. Through external field-assisted process innovation, the controllable construction of a nano-composite coating with high strength, toughness, and high wear resistance that imitates shell nacre layered structure is achieved.

[0015] Specifically, we systematically study the influence of chemical modification parameters, types of main elements of high-entropy alloys, process parameters, etc. on the microstructure and tribological properties of composite coatings, reveal the ion deposition law of high-entropy alloy coatings, clarify the formation process of the layered structure of composite coatings, and explain the tribological behavior characteristics of layered nanocomposite coatings. Finally, we develop a set of special technologies for functionalized graphene-enhanced high-entropy alloy composite coatings with good wear resistance, which provides certain technical support and theoretical basis for surface wear protection of key components.

[0016] Specifically, the surface magnetic functionalization modification and property characterization of graphene powder:

[0017] By screening metal elements with magnetic properties (Co, Fe, Ni) and changing the chemical modification process (solution concentration, solution pH value, time parameters), graphene composite powders loaded with single or multi-component nanometal particles based on Co, Fe, and Ni are obtained; the magnetic properties of the composite powders are detected by VSM, and the dispersion properties of the composite powders are investigated through physical sedimentation tests. The morphology, loaded particle size and composition of the composite powders are characterized by scanning electron microscopy, transmission electron microscopy, and X-ray diffractometer.

[0018] Electrodeposition of CoCrFeNi-M series high entropy alloy coating:

[0019] Through MS simulation, the lattice parameters, mechanical properties (elastic constants, Poisson's ratio), thermodynamic parameters (system formation enthalpy and free energy) and physical properties (conductivity) of CoCrFeNi-M (M=Al, Cu, Mn) high entropy alloys were clarified, and the M component was optimized; the influence of solution parameters such as the concentration ratio of the five main cations in the salt solution, the pH value of the solution, and the type of additives on the solid solution phase composition and element distribution of the high entropy alloy coating was systematically studied; then the single factor experimental method was used to adjust the electrodeposition parameters such as voltage, solution temperature, and deposition time to achieve the controllable preparation of the solid solution phase structure of the high entropy alloy.

[0020] X-ray diffractometer, scanning electron microscope, transmission electron microscope and electron backscatter diffractometer were used to characterize the phase structure of the coating, and thermodynamic calculations were assisted to clarify the solid solution phase formation mechanism of the high entropy alloy coating. The hardness of the coating was tested using a nanoindenter, and the bonding strength between the high entropy alloy coating and the metal substrate was obtained using a scratch tester. The influence of solution parameters and electrochemical process parameters on the performance of the high entropy alloy coating was explored, revealing the corresponding relationship between the type / content of the main element, process parameters and the microstructure and performance of the high entropy alloy coating.

[0021] Structural design and tribological behavior of functionalized graphene reinforced high entropy alloy composite coatings;

[0022] Using functionalized graphene as a precursor, layered composite coatings are prepared by controlling the electrodeposition process parameters and optimizing the parameters of external field-assisted tooling such as magnetic field / ultrasound. With the help of scanning electron microscopy, transmission electron microscopy, electron backscatter diffractometer, and X-ray diffractometer microscopic characterization methods, the influence of external field parameters such as electrodeposition method, magnetic field excitation frequency, working gap, and ultrasonic power on the distribution state of graphene and the microstructure of the coating is studied, and the formation mechanism of the layered composite coating is clarified.

[0023] A multi-environment friction and wear testing machine was used to characterize the tribological behavior of the layered composite coating under different test conditions (load, temperature, grinding medium, and rotation speed). A three-dimensional profilometer was used to measure the wear volume of the composite coating and calculate the wear rate. A laser confocal microscope was used to obtain the three-dimensional morphology of the wear scar. Raman spectrometer, X-ray diffractometer, scanning electron microscope and transmission electron microscope were used to analyze the structural evolution behavior of functionalized graphene in the friction test, the composition of the friction surface of the composite coating, structural changes, and wear products, thus revealing the friction and wear mechanism of the composite coating.

[0024] Specifically, the preparation and testing equipment includes: material performance simulation workstation (72-core server and 96-core server), electromagnetic stirring device, electrochemical deposition and other metal coating preparation equipment, ultrasonic processor, electromagnetic device, related field auxiliary tooling, microhardness tester, multi-environment friction and wear tester, step meter, optical microscope, nanoindentation test, electron probe microanalyzer, scanning electron microscope (equipped with EDS), backscattered electron diffraction device, transmission electron microscope, X-ray photoelectron spectrometer, X-ray diffractometer.

[0025] Beneficial effects of the present invention:

[0026] Graphene materials have broad application prospects in the field of friction due to their high strength, good conductivity, self-lubrication and other properties. By using graphene as a nano-additive phase, a graphene-enhanced metal-based nano-composite coating with excellent tribological properties is obtained. In addition, the development of chemical modification technology has solved the problem of poor compatibility between carbonaceous nanomaterials and metals, and made it possible to directional distribute graphene materials in metal matrices. Therefore, using modified graphene as a nano-additive phase, electrochemical technology is used to realize its co-deposition with multi-principal ions to form a modified graphene-enhanced high-entropy alloy composite coating, which further resists external loads and greatly improves the wear resistance of the high-entropy alloy coating.

[0027] In response to the wear-resistant protection requirements of key components such as aircraft landing gear support shafts and crankshafts, the surface structure of shell nacre is simulated, and through the innovation of graphene surface functionalization design and field-assisted electrodeposition process, a layered composite coating with high strength, toughness and high wear resistance is designed and controllably constructed.

[0028] Electrodeposited high-entropy alloy coatings can obtain thin layers composed of nanocrystals by controlling process parameters, so their mechanical properties are far superior to those of bulk high-entropy alloys with the same composition. Depositing them on the surface of damaged parts not only gives them excellent surface properties, but also maintains the original mechanical properties of the parts, greatly reducing costs.

[0029] The selection of ingredients is the basis for the performance of the coating, and the structural design is the key factor in improving the performance of the coating. As a typical layered nanostructure, "shell nacre" has the advantages of high toughness and good wear resistance, and has become a model structure for the preparation of high-strength and ultra-tough materials.

[0030] Through chemical modification technology, functional properties are given to graphene materials while solving the problems of weak interface bonding between graphene materials and metal matrix and poor dispersion in metal matrix. This assists in external field tooling design and realizes directional regulation of graphene powders. Based on the bionic structure model of shell nacre, with the help of functionalized graphene precursors and external field-assisted electrodeposition process innovation, the controllable construction of the layered structure of a new type of graphene-enhanced high-entropy alloy composite coating that combines strength, toughness and high wear resistance is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0032] Figure 1 The technical roadmap of the method for preparing the modified graphene-enhanced high-entropy alloy layered composite coating of the present invention;

[0033] Figure 2 Schematic diagram of electrodeposition of high entropy alloy coating;

[0034] Figure 3 The structure and mechanical properties of Cu-based composite materials with shell bionic structure; DETAILED DESCRIPTION

[0035] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0036] See also Figure 1-Figure 3 The present invention provides a technical solution: a method for preparing a modified graphene-enhanced high-entropy alloy layered composite coating, comprising the following steps:

[0037] Step 1: Graphene surface functionalization design and its directional regulation mechanism;

[0038] Using chemical modification technology, systematically study the influence of multi-element and multi-scale metal particle loading on the physical properties (dispersion, magnetic properties) of graphene material composite powders;

[0039] Screen and prepare modified graphene composite powders that can be controlled by external field, and reveal the distribution characteristics of composite powders during external field-assisted electrodeposition;

[0040] Step 2: Design of CoCrFeNi-M high entropy alloy coating and its electrodeposition mechanism;

[0041] Based on the first principles, the crystallographic parameters, thermodynamic properties and physical properties of CoCrFeNi-M (M=Al, Cu, Mn) high entropy alloys are simulated and predicted, and the types of M principal elements in the CoCrFeNi-M system are optimized to provide theoretical guidance for the principal element design of electrodeposited CoCrFeNi-M high entropy alloy coatings.

[0042] The influence of solution parameters and electrodeposition process parameters on the microstructure and properties of high entropy alloy coatings was systematically investigated. Combined with thermodynamic calculations, the deposition mechanism of the solid solution phase in high entropy alloy coatings was clarified, and the corresponding relationship between the main element type / element content, process parameters and coating microstructure and properties was established to screen out high entropy alloy coating systems with good forming quality.

[0043] Step 3: Structural design and tribological behavior of modified graphene-enhanced high-entropy alloy composite coating;

[0044] Optimize the external field assisted electrodeposition process parameters, realize the controllable regulation of the distribution state of functionalized graphene composite powder in high entropy alloy coating, construct gradient layered composite coating, and explore the organizational structure evolution law and regulation mechanism of composite coating under the action of electric field and external field;

[0045] The influence of different tribological test conditions on the tribological properties of composite coatings is studied, and the surface wear state, defect form and changing characteristics of graphene structure of the composite coating after the friction test are examined. The mapping relationship between process parameters, coating structure and tribological properties is clarified, and the structural design and controllable construction process of the composite coating are optimized through feedback.

[0046] Combining chemical modification technology with electrodeposition technology, chemical modification technology is used to evenly load nano-metal particles on the surface of graphene. This is used as a precursor, and through the optimization of electrodeposition process parameters, functionalized graphene-reinforced high-entropy alloy composite coatings are prepared. Through external field-assisted process innovation, the controllable construction of a nano-composite coating with high strength, toughness, and high wear resistance that imitates shell nacre layered structure is achieved.

[0047] A systematic study was conducted on the influence of chemical modification parameters, types of main elements of high-entropy alloys, process parameters, etc. on the microstructure and tribological properties of composite coatings. The ion deposition law of high-entropy alloy coatings was revealed, the formation process of the layered structure of the composite coatings was clarified, and the tribological behavior characteristics of the layered nanocomposite coatings were elucidated. Finally, a set of special technologies for functionalized graphene-enhanced high-entropy alloy composite coatings with good wear resistance was developed, providing certain technical support and theoretical basis for surface wear protection of key components.

[0048] Graphene powder surface magnetic functionalization modification and property characterization:

[0049] By screening metal elements with magnetic properties (Co, Fe, Ni) and changing the chemical modification process (solution concentration, solution pH value, time parameters), graphene composite powders loaded with single or multi-component nanometal particles based on Co, Fe, and Ni are obtained; the magnetic properties of the composite powders are detected by VSM, and the dispersion properties of the composite powders are investigated through physical sedimentation tests. The morphology, loaded particle size and composition of the composite powders are characterized by scanning electron microscopy, transmission electron microscopy, and X-ray diffractometer.

[0050] Electrodeposition of CoCrFeNi-M series high entropy alloy coating:

[0051] Through MS simulation, the lattice parameters, mechanical properties (elastic constants, Poisson's ratio), thermodynamic parameters (system formation enthalpy and free energy) and physical properties (conductivity) of CoCrFeNi-M (M=Al, Cu, Mn) high entropy alloys were clarified, and the M component was optimized; the influence of solution parameters such as the concentration ratio of the five main cations in the salt solution, the pH value of the solution, and the type of additives on the solid solution phase composition and element distribution of the high entropy alloy coating was systematically studied; then the single factor experimental method was used to adjust the electrodeposition parameters such as voltage, solution temperature, and deposition time to achieve the controllable preparation of the solid solution phase structure of the high entropy alloy.

[0052] X-ray diffractometer, scanning electron microscope, transmission electron microscope and electron backscatter diffractometer were used to characterize the phase structure of the coating, and thermodynamic calculations were assisted to clarify the solid solution phase formation mechanism of the high entropy alloy coating. The hardness of the coating was tested using a nanoindenter, and the bonding strength between the high entropy alloy coating and the metal substrate was obtained using a scratch tester. The influence of solution parameters and electrochemical process parameters on the performance of the high entropy alloy coating was explored, revealing the corresponding relationship between the type / content of the main element, process parameters and the microstructure and performance of the high entropy alloy coating.

[0053] Structural design and tribological behavior of functionalized graphene reinforced high entropy alloy composite coatings;

[0054] Using functionalized graphene as a precursor, layered composite coatings are prepared by controlling the electrodeposition process parameters and optimizing the parameters of external field-assisted tooling such as magnetic field / ultrasound. With the help of scanning electron microscopy, transmission electron microscopy, electron backscatter diffractometer, and X-ray diffractometer microscopic characterization methods, the influence of external field parameters such as electrodeposition method, magnetic field excitation frequency, working gap, and ultrasonic power on the distribution state of graphene and the microstructure of the coating is studied, and the formation mechanism of the layered composite coating is clarified.

[0055] A multi-environment friction and wear testing machine was used to characterize the tribological behavior of layered composite coatings under different test conditions. The test conditions included load, temperature, grinding medium, and rotation speed. A three-dimensional profilometer was used to measure the wear volume of the composite coating and calculate the wear rate. A laser confocal microscope was used to obtain the three-dimensional morphology of the wear scar. Raman spectrometer, X-ray diffractometer, scanning electron microscope, and transmission electron microscope were used to analyze the structural evolution behavior of functionalized graphene in the friction test, the composition of the friction surface of the composite coating, structural changes, and wear products, revealing the friction and wear mechanism of the composite coating.

[0056] Preparation and testing equipment include: material performance simulation workstation: 72-core server and 96-core server, electromagnetic stirring device, electrochemical deposition and other metal coating preparation equipment, ultrasonic processor, electromagnetic device, related field auxiliary tooling, microhardness tester, multi-environment friction and wear tester, step meter, optical microscope, nanoindentation test, electron probe microanalyzer, scanning electron microscope equipped with EDS, backscattered electron diffraction device, transmission electron microscope, X-ray photoelectron spectrometer, X-ray diffractometer.

[0057] High entropy alloys, which are composed of 5 or more alloying elements mixed in an equimolar ratio or a near-equimolar ratio, exhibit a unique solid solution structure, with each element accounting for 5%-35%. This multi-principal element combination will produce a serious lattice distortion effect, which makes it have excellent mechanical and physicochemical properties such as high specific strength, high hardness, high corrosion resistance and oxidation resistance. Therefore, high entropy alloys have broad tribological application prospects under complex working conditions. Among them, the electrodeposited high entropy alloy coating can obtain a thin layer of coating composed of nanocrystals by controlling the process parameters, so its mechanical properties are far better than those of bulk high entropy alloys with the same components. Depositing it on the surface of damaged parts not only gives it excellent surface properties, but also maintains the original mechanical properties of the parts, greatly reducing costs. Therefore, the electrodeposition of high entropy alloy coatings is an economical and effective way to improve the wear resistance of the surface of key parts.

[0058] Graphene materials have broad application prospects in the field of friction due to their high strength, good conductivity, self-lubrication and other properties. By using graphene as a nano-additive phase, a graphene-enhanced metal-based nano-composite coating with excellent tribological properties is obtained. In addition, the development of chemical modification technology has solved the problem of poor compatibility between carbonaceous nanomaterials and metals, and made it possible to directional distribute graphene materials in metal matrices. Therefore, using modified graphene as a nano-additive phase, electrochemical technology is used to realize its co-deposition with multi-principal ions to form a modified graphene-enhanced high-entropy alloy composite coating, which further resists external loads and greatly improves the wear resistance of the high-entropy alloy coating.

[0059] Graphene materials have broad application prospects in the field of friction due to their high strength, good conductivity, self-lubrication and other properties. By using graphene as a nano-additive phase, a graphene-enhanced metal-based nano-composite coating with excellent tribological properties is obtained. In addition, the development of chemical modification technology has solved the problem of poor compatibility between carbonaceous nanomaterials and metals, and made it possible to directional distribute graphene materials in metal matrices. Therefore, using modified graphene as a nano-additive phase, electrochemical technology is used to realize its co-deposition with multi-principal ions to form a modified graphene-enhanced high-entropy alloy composite coating, which further resists external loads and greatly improves the wear resistance of the high-entropy alloy coating.

[0060] In response to the wear-resistant protection requirements of key components such as aircraft landing gear support shafts and crankshafts, the surface structure of shell nacre is simulated, and through the innovation of graphene surface functionalization design and field-assisted electrodeposition process, a layered composite coating with high strength, toughness and high wear resistance is designed and controllably constructed.

[0061] Electrodeposited high-entropy alloy coatings can obtain thin layers composed of nanocrystals by controlling process parameters, so their mechanical properties are far superior to those of bulk high-entropy alloys with the same composition. Depositing them on the surface of damaged parts not only gives them excellent surface properties, but also maintains the original mechanical properties of the parts, greatly reducing costs.

[0062] The selection of ingredients is the basis for the performance of the coating, and the structural design is the key factor in improving the performance of the coating. As a typical layered nanostructure, "shell nacre" has the advantages of high toughness and good wear resistance, and has become a model structure for the preparation of high-strength and ultra-tough materials.

[0063] Through chemical modification technology, functional properties are given to graphene materials while solving the problems of weak interface bonding between graphene materials and metal matrix and poor dispersion in metal matrix. This assists in external field tooling design and realizes directional regulation of graphene powders. Based on the bionic structure model of shell nacre, with the help of functionalized graphene precursors and external field-assisted electrodeposition process innovation, the controllable construction of the layered structure of a new type of graphene-enhanced high-entropy alloy composite coating that combines strength, toughness and high wear resistance is achieved.

[0064] In response to the wear-resistant protection requirements of key components such as aircraft landing gear support shafts and crankshafts, the surface structure of shell nacre is simulated, and through the innovation of graphene surface functionalization design and field-assisted electrodeposition process, a layered composite coating with high strength, toughness and high wear resistance is designed and controllably constructed.

[0065] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a modified graphene-enhanced high-entropy alloy layered composite coating, characterized in that The following steps are involved: Step 1: Graphene surface functionalization design and its directional regulation mechanism; Using chemical modification technology, systematically study the influence of multi-element and multi-scale metal particle loading on the physical properties (dispersion, magnetic properties) of graphene material composite powders; Screen and prepare modified graphene composite powders that can be controlled by external field, and reveal the distribution characteristics of composite powders during external field-assisted electrodeposition; Step 2: Design of CoCrFeNi-M high entropy alloy coating and its electrodeposition mechanism; Based on the first principles, the crystallographic parameters, thermodynamic properties and physical properties of CoCrFeNi-M (M=Al, Cu, Mn) high entropy alloys are simulated and predicted, and the types of M principal elements in the CoCrFeNi-M system are optimized to provide theoretical guidance for the principal element design of electrodeposited CoCrFeNi-M high entropy alloy coatings. The influence of solution parameters and electrodeposition process parameters on the microstructure and properties of high entropy alloy coatings was systematically investigated. Combined with thermodynamic calculations, the deposition mechanism of the solid solution phase in high entropy alloy coatings was clarified, and the corresponding relationship between the main element type / element content, process parameters and coating microstructure and properties was established to screen out high entropy alloy coating systems with good forming quality. Step 3: Structural design and tribological behavior of modified graphene-enhanced high-entropy alloy composite coating; Optimize the external field assisted electrodeposition process parameters, realize the controllable regulation of the distribution state of functionalized graphene composite powder in high entropy alloy coating, construct gradient layered composite coating, and explore the organizational structure evolution law and regulation mechanism of composite coating under the action of electric field and external field; The influence of different tribological test conditions on the tribological properties of composite coatings is studied, and the surface wear state, defect form and changing characteristics of graphene structure of the composite coating after the friction test are examined. The mapping relationship between process parameters, coating structure and tribological properties is clarified, and the structural design and controllable construction process of the composite coating are optimized through feedback.

2. The method for preparing a modified graphene-enhanced high-entropy alloy layered composite coating according to claim 1, characterized in that: Combining chemical modification technology with electrodeposition technology, chemical modification technology is used to evenly load nano-metal particles on the surface of graphene. This is used as a precursor, and through the optimization of electrodeposition process parameters, functionalized graphene-reinforced high-entropy alloy composite coatings are prepared. Through external field-assisted process innovation, the controllable construction of a nano-composite coating with high strength, toughness, and high wear resistance that imitates shell nacre layered structure is achieved.

3. The method for preparing the modified graphene enhanced high entropy alloy layered composite coating according to claim 1, characterized in that: A systematic study was conducted on the influence of chemical modification parameters, types of main elements of high-entropy alloys, process parameters, etc. on the microstructure and tribological properties of composite coatings. The ion deposition law of high-entropy alloy coatings was revealed, the formation process of the layered structure of the composite coatings was clarified, and the tribological behavior characteristics of the layered nanocomposite coatings were elucidated. Finally, a set of special technologies for functionalized graphene-enhanced high-entropy alloy composite coatings with good wear resistance was developed, providing certain technical support and theoretical basis for surface wear protection of key components.

4. The method for preparing the modified graphene enhanced high entropy alloy layered composite coating according to claim 1, characterized in that: Graphene powder surface magnetic functionalization modification and property characterization: By screening metal elements (Co, Fe, Ni) with magnetic properties and changing the chemical modification process (solution concentration, solution pH value, time parameters), graphene composite powders loaded with single or multiple nanometal particles based on Co, Fe, and Ni are obtained; The magnetic properties of the composite powders were detected by VSM, and the dispersion properties of the composite powders were examined through physical sedimentation tests. The morphology, loaded particle size and composition of the composite powders were characterized by scanning electron microscopy, transmission electron microscopy and X-ray diffractometer. Electrodeposition of CoCrFeNi-M series high entropy alloy coating: Through MS simulation, the lattice parameters, mechanical properties (elastic constants, Poisson's ratio), thermodynamic parameters (system formation enthalpy and free energy) and physical properties (conductivity) of CoCrFeNi-M (M=Al, Cu, Mn) high entropy alloys were clarified, and the M component was optimized; the influence of solution parameters such as the concentration ratio of the five main cations in the salt solution, the pH value of the solution, and the type of additives on the solid solution phase composition and element distribution of the high entropy alloy coating was systematically studied; then the single factor experimental method was used to adjust the electrodeposition parameters such as voltage, solution temperature, and deposition time to achieve the controllable preparation of the solid solution phase structure of the high entropy alloy. X-ray diffractometer, scanning electron microscope, transmission electron microscope and electron backscatter diffractometer were used to characterize the phase structure of the coating, and thermodynamic calculation was assisted to clarify the solid solution phase formation mechanism of the high entropy alloy coating. The hardness of the coating was tested using a nanoindenter, and the bonding strength between the high entropy alloy coating and the metal substrate was obtained using a scratch tester. To explore the influence of solution parameters and electrochemical process parameters on the performance of high entropy alloy coatings, and reveal the corresponding relationship between the type / content of the main element, process parameters and the microstructure and properties of high entropy alloy coatings; Structural design and tribological behavior of functionalized graphene reinforced high entropy alloy composite coatings; Using functionalized graphene as a precursor, layered composite coatings are prepared by controlling the electrodeposition process parameters and optimizing the parameters of external field-assisted tooling such as magnetic field / ultrasound. With the help of scanning electron microscopy, transmission electron microscopy, electron backscatter diffractometer, and X-ray diffractometer microscopic characterization methods, the influence of external field parameters such as electrodeposition method, magnetic field excitation frequency, working gap, and ultrasonic power on the distribution state of graphene and the microstructure of the coating is studied, and the formation mechanism of the layered composite coating is clarified. A multi-environment friction and wear tester was used to characterize the tribological behavior of the layered composite coating under different test conditions (load, temperature, grinding medium, rotation speed). A three-dimensional profilometer was used to measure the wear volume of the composite coating and calculate the wear rate, and a laser confocal microscope was used to obtain the three-dimensional morphology of the wear scar. Raman spectrometer, X-ray diffractometer, scanning electron microscope and transmission electron microscope were used to analyze the structural evolution behavior of functionalized graphene in the friction test, the composition, structural changes and wear products of the friction surface of the composite coating, revealing the friction and wear mechanism of the composite coating.

5. The method for preparing the modified graphene enhanced high entropy alloy layered composite coating according to claim 4, characterized in that: Preparation and testing equipment include: material performance simulation workstation (72-core server and 96-core server), electromagnetic stirring device, electrochemical deposition and other metal coating preparation equipment, ultrasonic processor, electromagnetic device, related field auxiliary tooling, microhardness tester, multi-environment friction and wear tester, step meter, optical microscope, nanoindentation test, electron probe microanalyzer, scanning electron microscope (equipped with EDS), backscattered electron diffraction device, transmission electron microscope, X-ray photoelectron spectrometer, X-ray diffractometer.